Guest Editorial: Identification, Stability Analysis, Control and Situation Awareness of Power Systems With High Penetrations of Renewable Energy Resources - Lie, Tek Tjing; Luan, Wenpeng (John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology, 2024)
It is with great pleasure that the authors introduce this special issue, commemorating the 8th Asia Conference on Power and Electrical Engineering held in Tianjin in 2023. This conference served as a nexus for researchers, practitioners, and industry experts from around the globe to convene and exchange cutting-edge insights, innovative ideas, and transformative advancements in the field of power and electrical engineering. The contributions featured in this special issue represent a diverse array of research endeavours, spanning from fundamental theories to practical applications, all aimed at addressing the myriad challenges and opportunities facing the power and electrical engineering domain. From novel methodologies in renewable energy integration to advancements in smart grid technologies, each article encapsulates the spirit of innovation and collaboration that characterised the conference. This special issue includes scientific investigations on topology modelling and virtual stability analysis methods for distribution networks with high penetration of renewable energy resources, monitoring and situation awareness on grid inertia and power-frequency evolution, novel voltage source converter control schemes, and reviews of low-carbon planning and operation of electricity, hydrogen fuel, and transportation networks.
Keywords: distributed power generation, electric vehicles, photovoltaic power systems, power generation control